Adult Wilms Tumor With Inferior Vena Cava Thrombus on an Incomplete Duplex Collecting System Ureter Fissus Proximalis Managed at a Tertiary Hospital in Tanzania: A Case Report and Literature Review - Amini Mitamo Alexandre; Joseph Martin Lori; Gabriel F. Mtaturu; Victor Patrick Sensa; Sylvia Bedas Nsato; Mariam Athumani Mbezi; Obadia V. Nyongole; Charles A. Mkony (Clinical Case Reports)
ABSTRACT Wilms' tumor (WT), also known as nephroblastoma, is a malignant embryonal kidney tumor composed of embryonic cells and is the most prevalent tumor among children, but isolated cases occur infrequently in the adult population. Adult WT is defined according to the criteria of Kilton, Matthews, and Cohen, which comprise age above 15 years and histological patterns characteristic of WT. We report a case of an adult WT with venous thrombus on an incomplete duplex collecting system. To the best of our knowledge, this is the first case of adult WT with such a presentation. A 28‐year‐old female patient presented to our department with a 4‐month history of right flank pain and flank mass and was diagnosed by abdominal contrasted CT to have a right renal tumor with tumor thrombi in the renal vein and the inferior vena cava. The CT scan also revealed a bilateral duplex collecting system with a partial (ureter fissus proximalis) on the tumor side and a complete duplex system on the contralateral side. Right radical nephrectomy with complete tumor thrombectomy via venacavotomy was performed successfully. Histopathological examination of the specimen revealed a triphasic nephroblastoma with immunohistochemistry confirmation. Postoperatively, adjuvant chemotherapy was initiated. The increasing incidence of non‐syndromic WT cases associated with duplex collecting systems suggests a potential shared pathogenesis, necessitating further research.